Kreasi origami / oleh Eileen o'brien, Kate Needham ; editor, Fiona Watt, Kiki Sulistiyani, Margaretha H Eddy - O'BRIEN, Eileen; Needham, Kate; Watt, Fiona; Sulistiyani, Kiki; Eddy, Margaretha H (Erlangga)
31 hlm ilus 28 cm